2020
DOI: 10.1007/s40474-020-00206-w
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, Acceptance and Belonging for People with IDD Across Cultures

Abstract: Purpose of Review This review explores recent literature (from 2017 onwards) to identify current developments related to reducing stigma and increasing acceptance for people with Intellectual and Developmental Disabilities (IDD) in their communities across diverse cultures. Recent Findings We identified literature related to experiences of stigma for people with IDD and their families across diverse cultures, as well as current and potential interventions and approaches for promoting acceptance. Summary Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 83 publications
0
23
0
Order By: Relevance
“…Importantly, when developing the model we considered the definition of stigma broadly and also incorporated relevant research on attitudes and acceptance, which are correlates of stigma and theoretically tightly coupled. 8,46 Our narrative approach was underpinned by a thorough PubMed review of articles on autism (autis*) paired systematically with each of the following terms stigma, attitude, understanding, knowledge.…”
Section: Affiliate/courtesy Stigmamentioning
confidence: 99%
“…Importantly, when developing the model we considered the definition of stigma broadly and also incorporated relevant research on attitudes and acceptance, which are correlates of stigma and theoretically tightly coupled. 8,46 Our narrative approach was underpinned by a thorough PubMed review of articles on autism (autis*) paired systematically with each of the following terms stigma, attitude, understanding, knowledge.…”
Section: Affiliate/courtesy Stigmamentioning
confidence: 99%
“…Other factors are the seemingly and unfavorable cultural beliefs associated with IDD, which awaits the parents and their children with IDD in most low‐income countries, family stigma, and discrimination (Bakare et al, 2009; Jansen‐van Vuuren & Aldersey, 2020; Skinner & Weisner, 2007). These factors can facilitate higher risks of neglect, maltreatment, violence, family disintegration, exclusion from formal education, and full economic participation and even premature death (Oti‐Boadi et al, 2020; Wang et al, 2020).…”
Section: Family Quality Of Lifementioning
confidence: 99%
“…Studies have shown that individuals with IDD generally receive insufficient attention and support within public health research (Krahn et al, 2015). Despite the legislations of the United Nations Convention on the Rights of Persons with Disabilities aimed at upholding the dignities and human rights of disabled people, these individuals are faced with stigmatization that hinders social inclusion and increases inequalities when compared with the general population across the globe (Jansen‐van Vuuren & Aldersey, 2020). This is challenging in Nigeria, where the predominant cultural and religious beliefs are that people are disabled because of either their misdeeds, parental transgressions, witchcraft, cursed from God, or possessed by evil spirits (Ajuwon, 2012; Oloyede, 2011), and as such these individuals are often marginalized and stigmatized.…”
Section: Why Nigeria?mentioning
confidence: 99%